Designing A Motion Graphic Company Profile Video for pt Privy Digital Identity - Juanda, Edwar; Pratama , Bagas (Asian Journal of Social and Humanities, 2025)
Business competition in the increasingly advanced digital era, the need to strengthen the image of a business through digital media is important, especially for companies such as PT Privy Digital Identity which is engaged in certified digital signature services. This design aims to create promotional media in the form of a video company profile based on motion graphic techniques that can improve the image of Privy company for the better. The choice of motion graphics as a promotional medium is due to its ability to simplify complex information and package it attractively through a persuasive combination of animation, graphics, and narrative. The methodology applied in the design is Design Thinking, which involves the stages of Empathize, Define, Ideate, Prototype, and Test. This stage helps to develop an audience-centric design strategy to solve existing visual communication problems. Trials are carried out to measure the effectiveness of the work in achieving the design objectives. The results of the trial show that a company profile based on motion graphic techniques can be an effective medium to improve the company's image, by providing important information needed by the audience through attractive visual presentations.